Usuń nawiasy i zredukuj wyrazy podobne:
a) -1,2xy-8y²-(-5yx+10(całych) i 1/2y² -8,3)-(-2,3+3,8xy)=
b) 8a²bc-(4abc²+10acb²)-[-(4c²ab+10ab²c)-8bca²]=
c) (3(całych i 1/2x²-7,5y)-5-(1(cała) i 1/2y+5,5x²-3,2)+2x²+9y=
d) -3,2+(-0,8+2z)-(1,2y-0,8x)-(2z-2,4x)=

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T17:30:15+01:00
A) -1,2xy-8y²-(-5yx+10(całych) i 1/2y² -8,3)-(-2,3+3,8xy)= -1,2xy -8y² +5xy -10 i 1/2 y² +8,3 +2,3 -3,8xy = -18,5y² +10,6
b) 8a²bc-(4abc²+10acb²)-[-(4c²ab+10ab²c)-8bca²]= 8a²bc -4abc² -10ab²c -[-4c²
-ab -10ab²c -8a²bc]= 8a²bc -4abc²-10ab²c +4c² +ab +10ab²c +8a²bc= 16a²bc -
4abc² +4c² +ab
c) (3(całych i 1/2x²-7,5y)-5-(1(cała) i 1/2y+5,5x²-3,2)+2x²+9y= 3,5x² -7,5y -7,5y -27,5x² +16 +2x² +9y = -22x² -6y +16
d) -3,2+(-0,8+2z)-(1,2y-0,8x)-(2z-2,4x)= -3,2 -0,8 +2z -1,2y +0,8x -2z +2,4x = -4 -1,2y +3,2x